Returning to life activities after hematopoietic cell transplantation in older adults. Issue 2 (March 2020) - Koll, Thuy T.; Semin, Jessica N.; Coburn, Rachel A.; Hill-Polerecky, Diane M.; Miller, Kimberly A.; Wildes, Tanya M.; Estabrooks, Paul A.; Jones, Katherine J.
Abstract: Objectives: The prevalence of hematopoietic cell transplant (HCT) among older adults with hematological malignancies has more than doubled over the last decade and continues to grow. HCT is an intense process that can impact functional status and health-related quality of life. The objective of this paper is to describe the experience of returning to life activities after HCT in patients 60 years of age and older and the resources required to adapt and cope to limitations in physical, psychological, and cognitive function. Materials and Methods: Twenty English speaking adults 60 years and older with hematological malignancy 3 to 12 months post-HCT completed semi-structured interviews. Open-ended questions and probes were guided by the Transactional Model of Stress and Coping to explore adaptive functioning, coping resources, and coping strategies. An integrated grounded theory approach was used to code the textual data to identify themes. The study took place at a tertiary comprehensive cancer center in the Midwest United States. Results: Eight allogeneic and twelve autologous HCT recipients participated in the interviews. Nineteen participants were within 6–12 months and 1 participant was at 3 months post-HCT. Our findings identify the significant role of engaging in life activities and social support in the recovery of physical, psychological and cognitive function. Conclusion: Older HCT recipients are an understudied population. They are at high risk for functional decline. Our findings may provide community oncologists and primary care physicians with a context for providing care to older HCT survivors during their recovery.